2012
DOI: 10.1039/c2py20155k
|View full text |Cite
|
Sign up to set email alerts
|

Thiol-Michael coupling chemistry: facile access to a library of functional exo-7-oxanorbornenes and their ring-opening metathesis (co)polymerization

Abstract: The nucleophile initiated thiol-Michael reaction of a wide range of mono and multifunctional thiols with a novel acrylic exo-7-oxanorbornene is described. We highlight how this process affords ready access to a large library of thioether-based substrates in a quick and convenient fashion. New substrates containing, for example, ester, fluoro, and siloxy functionality polymerized in a controlled fashion with Grubbs' first generation (G1) catalyst, RuCl 2 (PCy 3 ) 2 CHPh, yielding homopolymers with controlled, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 64 publications
1
29
1
Order By: Relevance
“…The primary aim of this work was to evaluate the ability to prepare highly functional, ROMP‐active dendron monomers based on the exo ‐7‐oxanorbornene structural motif employing straightforward thiol‐Michael click chemistry. Given our previous work with thioether‐based monofunctional ROMP‐active monomers and the synthesis of hyperbranched (co)polymers from difunctional substrates, we initially targeted the diacrylate and tetraacrylate functional dendron species G1 and G2 that would serve as common substrates in subsequent nucleophile‐mediated thiol‐Michael reactions. G1 and G2 were prepared via multistep procedures as outlined in Scheme .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary aim of this work was to evaluate the ability to prepare highly functional, ROMP‐active dendron monomers based on the exo ‐7‐oxanorbornene structural motif employing straightforward thiol‐Michael click chemistry. Given our previous work with thioether‐based monofunctional ROMP‐active monomers and the synthesis of hyperbranched (co)polymers from difunctional substrates, we initially targeted the diacrylate and tetraacrylate functional dendron species G1 and G2 that would serve as common substrates in subsequent nucleophile‐mediated thiol‐Michael reactions. G1 and G2 were prepared via multistep procedures as outlined in Scheme .…”
Section: Resultsmentioning
confidence: 99%
“…The reaction is rapid, requires very low levels of either amine or phosphine as the initiating species, generally gives quantitative formation of the thiol‐Michael adduct and has been shown to be superior to the more commonly employed base‐mediated thiol‐Michael reaction. Recently, for example, we reported the synthesis of a novel acrylate‐bearing exo ‐7‐oxanorbornene, (2‐((3a R ,7a S )‐1,3‐dioxo‐3a,4,7,7a‐tetra‐hydro‐1 H ‐4,7‐epoxyisoindol‐2(3 H )‐yl)ethyl acrylate), and demonstrated how from this single readily accessible molecule a wide range of monofunctional and difunctional thioether‐based ring‐opening metathesis polymerization (ROMP) active substrates could be prepared quickly via phosphine‐mediated conjugate addition reactions. The resulting thioether adducts were demonstrated to undergo controlled ROMP yielding well‐defined (co)polymers in the case of the monofunctional adducts and hyperbranched (co)polymers for the difunctional species.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of Monomer M3 : Step 1 : Synthesis of Z5 (3a,4,7,7a‐Tetrahydro‐2‐(2‐hydroxyethyl)‐4,7‐epoxy‐1H‐isoindole‐1,3(2H)‐dione) . The synthesis was performed as reported in the literature . Exo ‐3,6‐Epoxy‐1,2,3,6‐tetrahydrophthalic acid anhydride ( R1 , 8.3 g, 50 mmol, 1 eq.)…”
Section: Discussionmentioning
confidence: 99%
“…As such, one desirable goal in the ROMP arena is the facile access to a suite of functional monomers employing non‐demanding and straightforward chemistry. In an effort to address this issue, Liu et al recently reported the synthesis and (co)polymerization of a library of thioether‐based exo ‐7‐oxanorbornenes obtained employing nucleophilic thiol‐Michael coupling with a common substrate (Scheme ).…”
Section: Discussionmentioning
confidence: 99%